М.Х. Дулати шығармашылығындағы ұлттық тарих философиясын зерделеудің концептуалдық негіздері - Zh. E., Myrzabekov; G.Zh., Nurysheva; Zh., Amirkulova; M.A., Dombayci (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2020)
This article discusses the importance of the study of the national history of philosophy in order to revive the national code and national identity, as fundamental in the development of the people. From the same point of view, the conceptual foundations of the work of the great thinker of the Middle Ages M.Kh.Dulati are analyzed. Deep knowledge in any period of national history, as well as a worthy and truthful assessment of this, promises a bright future for the people, in connection with which the need for comprehensive studies of the historical and philosophical significance of the philosophical views of M.Kh.Dulati is important. The main conclusion of the work today is the relevance for Turkic civilization of the need for a comprehensive study of the previous endeavors of an original culture and the definition of the conceptual foundations of the system of cultural and historical values of the East. Along with this, trends on current issues of Kazakhstani society in the era of globalization and bringing factors in favor of the fact that Turkic civilization is a very necessary structure in the development of national culture are considered. The authors, in particular, have identified ways to study cultural and historical values in line with an in-depth analysis of the philosophical heritage of M.Kh.Dulati, the development of dulatation in national philosophy. According to the author, the conceptual basis should be the promotion of historical events, historical figures, the health of the past, which make a significant contribution to our development today. Key words: national history, conceptual foundations, Dulati, philosophy, value, civilization.